Markerless visual servo control of a servosphere for behavior observation of a variety of wandering animals. (16th February 2019) - Iwatani, Yasushi; Ogawa, Hiroto; Shidara, Hisashi; Sakura, Midori; Sato, Takuya; Hojo, Masaru K.; Honma, Atsushi; Tsurui-Sato, Kaori
ABSTRACT: Servospheres are robotized observation equipments that produce endless fields for behavior observation of wandering animals. This paper first proposes a markerless visual tracking technique for estimation of the position and the heading direction of wandering animals, since existing techniques for servospheres require special markers or do not estimate the heading direction. The proposed markerless visual tracking technique is then integrated with a visual servo controller for a servosphere. The integrated markerless visual servo controller is available for wandering animals whose shapes in the image plane are represented by long bodies and thinner parts than their bodies. This paper demonstrates that the proposed controller is available for ants, crickets, mantises and spiders, while the shapes of their bodies and legs are different from each other. GRAPHICAL ABSTRACT: